MODELING CHEMISTRY ASPIRATIONS IN HIGH SCHOOL: A STRUCTURAL EQUATION APPROACH TO SELF-EFFICACY, LEARNING APPROACHES, AND SELF-REGULATED LEARNING - Nasihah, Durrotun; Sutrisno, Hari (Science Education, Institut Agama Islam Negeri Ponorogo, 2025)
This study aims to (1) identify the best model of relationships among learning self-efficacy, learning approaches, and self-regulated learning on the chemistry aspirations of high school students during the pandemic, and (2) determine the structural equation model (SEM) that best represents these relationships, including the relevant dimensions and indicators for each variable. This quantitative research employed a survey method, path analysis, and SEM approach. The sample consisted of 603 students from the Cirebon district, selected through cluster random sampling. Data were collected using a structured questionnaire. Prior to statistical analysis, prerequisite tests including normality, homogeneity, and outlier detection were conducted. Validity and reliability were examined using Exploratory and Confirmatory Factor Analyses.The findings revealed that the learning approach had the most significant direct association with students’ chemistry aspirations, whereas self-efficacy and self-regulated learning showed indirect relationships. Interestingly, surface motives rather than deep strategies were found to be more strongly linked to chemistry aspirations, suggesting that students’ engagement is primarily driven by performance goals and exam success. This context-dependent finding reflects Indonesia’s teacher-centered and exam-oriented learning culture. The most influential indicator was students’ initiative to use their free time to explore chemistry topics, while the least influential was self-control during unsupervised study. These results highlight the need to design learning strategies that gradually transform surface motives into deeper, intrinsic engagement through reflective, inquiry-based, and feedback oriented learning.